Congenital Anomalies of the Kidney and Urinary Tract in Children with Congenital Heart Defects - Dapeng Jiang; Qi Wang; Zhengzhou Shi; Jie Sun (Karger Publishers, 2020)
Background/Aims: To investigate the incidence and clinical characteristics of congenital anomalies of the kidney and urinary tract (CAKUT) in children with congenital heart defects (CHD). Methods: We retrospectively analyzed the clinical data of children with CHD with CAKUT admitted to the Shanghai Children's Medical Center affiliated with the Shanghai Jiao Tong University School of Medicine between September 2018 and March 2019. Patients underwent routine examinations for liver, kidney, and coagulation function, and urinary tract ultrasonography, and we summarized patients' clinical manifestations and imaging abnormalities. Results: A total of 1,410 children with CHD were diagnosed and treated in our hospital. The total number of patients with abnormal urogenital systems was 104, and hydronephrosis was the most common abnormality, followed by vesicoureteral reflux and duplication of the kidney and ureter. The overall prevalence of CAKUT was 7.4%. There was no statistically significant difference for maternal age, sex, parity, gestational age, and history of medication during pregnancy between the patients with CAKUT and those without CAKUT. Conclusion: The incidence of CAKUT in our patients with CHD was significantly higher than that in the general population. We recommend urinary ultrasonography as a routine examination for children with CHD for early detection of CAKUT, to avoid missed diagnoses, and to initiate appropriate treatment.